Leaf trait variation during ontogeny in the endangered Brazilian rosewood tree - Souza, M. L.; Garcia, L. E.; Lovato, M. B.; Lemos‐Filho, J. P.; Byers, D. (Plant biology (Stuttgart, Germany), 2021)
Knowledge of plant responses to environmental heterogeneity during ontogeny is important to elucidate the changes that occur to promote resource capture in tropical forests. We tested the hypothesis that expression changes in leaf metamer traits of Brazilian rosewood (Dalbergia nigra), from seedlings to emergent canopy trees, occur as new microclimate environments are achieved. We also tested the hypothesis that increased light heterogeneity in the understorey leads to higher plasticity in leaf traits of seedlings and saplings than in sun‐exposed metamers of emergent trees subject to stressful conditions. We compared leaf metamer traits of 53 individuals including seedlings, saplings and emergent trees. We also evaluated the light heterogeneity in vertical strata and the variations in leaf traits within individuals (among metamers of the same individual). These were associated with height of the individuals. Compared to understorey plants, emergent trees presented larger metamers, with lower specific leaf area (SLA), lower investment in leaf area per total dry mass of metamer (LARm), lower specific petiole length (SPL) and lower specific internode length (SIL). Higher phenotypic variation within individuals was observed in seedlings, which decreased as the trees grew taller. The results suggest the integration of ontogenetic changes in leaf traits under new microclimate conditions as the plants reach different vertical strata in the forest. Additionally, our results support the hypothesis that increased light heterogeneity in the understorey shaped higher phenotypic variation within individuals in juveniles and that stressful conditions in sun‐exposed leaf metamers of emergent trees led to increased phenotypic stability. Changes in leaf metamer traits during ontogeny in the Brazilian rosewood are associated with the new microclimate conditions during plant growth.